2017
DOI: 10.1016/j.cognition.2017.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizing agency: Folkpsychological and folkcommunicative perspectives on plants

Abstract: The present research addresses cultural variation in concepts of agency. Across two experiments, we investigate how Indigenous Ngöbe of Panama and US college students interpret and make inferences about nonhuman agency, focusing on plants as a critical test case. In Experiment 1, participants predicted goal-directed actions for plants and other nonhuman kinds and judged their capacities for intentional agency. Goal-directed action is pervasive among living kinds and as such we expected cultural agreement on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 93 publications
(112 reference statements)
1
40
0
1
Order By: Relevance
“…Our initial analyses took a broad look by collapsing across the specific capacities (thought, desire, etc.) for an overall measure of “agency.” As predicted, results from several experiments have shown that Ngöbe are more likely than US participants to attribute agency to plants and abiotic kinds based on their capacity to interact with the environment, as compared to US participants who are relatively more likely to attribute agency to complex artifacts due to their human‐designed information processing capacities (Ojalehto, Medin, and Garcia 2017a; Ojalehto, Medin, and Garcia 2017b) (see Figure 1). 3 Looking within the Ngöbe results more closely, we see that plants are ascribed agency at levels closer to that of animals than artifacts, suggesting that agency is seen as a shared property of vegetal and animal kinds.…”
Section: Current Research: Cognitive Psychological Studies On the Newmentioning
confidence: 60%
See 1 more Smart Citation
“…Our initial analyses took a broad look by collapsing across the specific capacities (thought, desire, etc.) for an overall measure of “agency.” As predicted, results from several experiments have shown that Ngöbe are more likely than US participants to attribute agency to plants and abiotic kinds based on their capacity to interact with the environment, as compared to US participants who are relatively more likely to attribute agency to complex artifacts due to their human‐designed information processing capacities (Ojalehto, Medin, and Garcia 2017a; Ojalehto, Medin, and Garcia 2017b) (see Figure 1). 3 Looking within the Ngöbe results more closely, we see that plants are ascribed agency at levels closer to that of animals than artifacts, suggesting that agency is seen as a shared property of vegetal and animal kinds.…”
Section: Current Research: Cognitive Psychological Studies On the Newmentioning
confidence: 60%
“…Our account of folkcommunication predicts instead that animism may scaffold productive inferences about ecological behavior. To test this, we designed an experiment to assess intuitive expectations for plant behavior in novel reasoning scenarios (Ojalehto, Medin, and Garcia 2017a). The logic behind using novel reasoning scenarios (rather than familiar topics such as one's own gardening practices) is that they demand using conceptual knowledge productively to generate inferences about new problems rather than fact retrieval based on prior knowledge, making visible inferential principles.…”
Section: Current Research: Cognitive Psychological Studies On the Newmentioning
confidence: 99%
“…There are some existing psychological studies that show that both culture and religious beliefs can affect how individuals reason about minds. Work with the Ngöbe people of Panama has found that the Ngöbe use ecological and social relationships, rather than animacy and consciousness, as a basis for agency (ojalehto et al., ,b). This is illustrated by the finding that the Ngöbe include plants and abiotic entities in their category of things that have agency and a capacity for intentional actions along with animals or humans.…”
Section: Cultural Differences In Conceiving Of and Reasoning About Mindsmentioning
confidence: 99%
“…These abilities, and the ability to socially learn and transmit knowledge that comes with them, are part of the foundation of our remarkable ability to create the myriad of different cultures we live in (Chudek & Henrich, ; Chudek, Zhao, & Henrich, ; Henrich, ). These cultural differences can, in turn, affect how we conceive of and reason about minds (e.g., ojalehto, Medin, & García, ,b). Some of the most striking examples of how culture can influence mind concepts are in how we understand the minds of gods and spirits (Astuti & Harris, ; D'Andrade, ; Knight, ; Knight, Sousa, Barrett, & Atran, ; Lane, Wellman, & Evans, ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these ethnographic observations, there are intriguing cross-cultural similarities in animist ontologies. Indigenous communities around the world tend to be much more permissive in their ascription of intentionality than Western participants (Ojalehto, Douglas, & García, 2017).…”
Section: Introductionmentioning
confidence: 98%